Carrying progeny on the back: reproduction in the Brazilian aquatic frog Pipa carvalhoi - Fernandes, Tatiana L.; Antoniazzi, Marta Maria; Sasso-Cerri, Estela [UNESP]; Egami, Mizue Imoto; Lima, Carla; Rodrigues, Miguel Trefaut Urbano; Jared, Carlos (Brazilian Herpetological Society, 2011)
Female Pipa carvalhoi incubate their eggs in the skin of the dorsum where the embryos develop until they emerge. Behavioral and morphological aspects of this reproductive mode were studied through courtship until the tadpoles emerged. Samples of the female skin were collected beginning a few hours after egg deposition and through subsequent phases of larval development and examined using standard histology, histochemistry and immunohistochemistry. The females' dorsal skin structure changes during egg implantation and development. These changes may be mediated by hormones and enzymes in a manner paralleling that of trophoblast implantation in mammal endometrium. The lack of vittelum and the extensive vascularization in the female after the 14th day of egg implantation suggest interaction through blood between the female and embryos. This hypothesis could be better accessed, if comparisons could be made with similar species such as Pipa pipa and Pipa arrabali, in which the embryos hatch only after metamorphosis. Similar observations have been made for marsupial frogs of the genus Gastrotheca in which some females maintain the embryos in a pouch in the dorsal integument. For P. carvalhoi, at least within populations of the Brazilian semi-arid environment (Caatinga), where bodies of water and rivers are temporary and depend on the short rainy season, this type of reproduction may be important for the rapid dissemination of large numbers of progeny.
Keywords: Amphibia; Anura; Pipidae; Pipa carvalhoi; Skin morphology; Reproduction; Behavior; Nuptial dance